Immunomodulatory Effects of Probiotics: A Novel Preventive Approach for the Control of Bovine Mastitis - A. K. M. Humayun Kober; Sudeb Saha; Md. Aminul Islam; Muhammad Shahid Riaz Rajoka; Kohtaro Fukuyama; Hisashi Aso; Julio Villena; Haruki Kitazawa (Microorganisms, 2022)
Bovine mastitis (BM) is one of the most common diseases of dairy cattle, causing economic and welfare problems in dairy farming worldwide. Because of the predominant bacterial etiology, the treatment of BM is mostly based on antibiotics. However, the antimicrobial resistance (AMR), treatment effectiveness, and the cost of mastitis at farm level are linked to limitations in the antibiotic therapy. These scenarios have prompted the quest for new preventive options, probiotics being one interesting alternative. This review article sought to provide an overview of the recent advances in the use of probiotics for the prevention and treatment of BM. The cellular and molecular interactions of beneficial microbes with mammary gland (MG) cells and the impact of these interactions in the immune responses to infections are revised. While most research has demonstrated that some probiotics strains can suppress mammary pathogens by competitive exclusion or the production of antimicrobial compounds, recent evidence suggest that other probiotic strains have a remarkable ability to modulate the response of MG to Toll-like receptor (TLR)-mediated inflammation. Immunomodulatory probiotics or immunobiotics can modulate the expression of negative regulators of TLR signaling in the MG epithelium, regulating the expression of pro-inflammatory cytokines and chemokines induced upon pathogen challenge. The scientific evidence revised here indicates that immunobiotics can have a beneficial role in MG immunobiology and therefore they can be used as a preventive strategy for the management of BM and AMR, the enhancement of animal and human health, and the improvement of dairy cow milk production.